Child maltreatment and alcohol outlets in Spain: Does the country drinking culture matters?. (May 2019) - Marco, Miriam; Gracia, Enrique; López-Quílez, Antonio; Freisthler, Bridget
Abstract: Background: Alcohol outlet density has been linked to rates of substantiated maltreatment both cross-sectionally and over time. Most of these studies have been conducted in Anglo-Saxon countries, especially in the U.S., but other countries, where alcohol outlets and alcohol consumption may have different social meanings, are clearly underrepresented in the literature. Objective: The aim of this study was to analyze whether alcohol outlet density is associated with neighborhood-level child maltreatment risk in a South-European city. Participants and setting: A longitudinal study was conducted in the city of Valencia (Spain). As spatial units, we used 552 census block groups. Family units with child maltreatment protection measures from 2004 to 2015 were geocoded (n = 1799). Methods: A Bayesian spatio-temporal autoregression model was conducted to model the outcome variable. Results: Results indicated that, once controlled for other neighborhood-level characteristics, the influence of off-premise density and restaurant/cafe density were not relevant, while bar density showed a negative relationship with child maltreatment risk. Spatially lagged alcohol outlet variables were also not relevant in the model. Conclusions: Our results suggest the importance of taking into account the cultural influences on the relationship between alcohol outlets and child maltreatment risk. Future cross-cultural research is needed for better understanding this relationship.